The Precambrian Shield of northernmost Baffin Bay: correlation across Nares Strait - Frisch, Thomas; Dawes, Peter R. (Meddelelser om Grønland. Geoscience, 1982)
The northern rim of the North American craton outcrops in the Baffin Bay – Nares Strait region where it forms large parts of southeastern Ellesmere Island and northwestern Greenland. Between 76°N and 78°N the Precambrian Shield comprises high-grade gneiss and metasediments which show a comparable chronological history in Ellesmere Island and Greenland. Two major features that emphasise the close relationship between the Shield on either side of Nares Strait are the presence of marble-rich metasedimentary tracts and a distinctive suite of late Archaean granitic to basic plutonic rocks which have locally been transformed by intense Proterozoic (probably Hudsonian) deformation into complexly folded orthogneisses. Marble-rich tracts are common throughout southeastern Ellesmere Island: in northwestern Greenland they are restricted to Inglefield Land north of 78°N. The regional structure suggests that the marble-rich tracts constitute a single marble province and that those on opposite sides of Smith Sound at Cape Isabella (Canada) and Sunrise Pynt (Greenland) may well represent on-strike parts of the same belt of supracrustal rocks. Correlation of the distinctive features of the Shield in southeastern Ellesmere Island and northwestern Greenland is entirely consistent with there having been no major strike-slip movement along Nares Strait.